Décomposer les humanités numériques - Michael Piotrowski; Aris Xanthos (Humanités Numériques)
The definition of the digital humanities has been a matter of heated discussion ever since the introduction of the term, earning the field the dubious reputation of being undefinable. While some seem to take pride in this reputation, the absence of a coherent definition frequently sparks off acrimonious criticism and debates. More importantly, though, it increasingly becomes a liability in the context of the progressive institutionalisation of the digital humanities.Rather than vainly trying to find a definition of digital humanities that is at the same time descriptive and rigorous, we propose a stipulative definition that separates them into theoretical and applied digital humanities: the theoretical digital humanities are the metascientific discipline whose goal is the conception of formal methods that the applied digital humanities use to create formal models in the various humanities disciplines.